2010
DOI: 10.1111/j.1472-765x.2009.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for preventing spread of fungi in air-conditioning systems constructed using copper instead of aluminium

Abstract: Aims:  As copper has been previously suggested as an antimicrobial surface, we tested the effectiveness of copper as an antifungal surface which could be used in air‐conditioning systems as an alternative to aluminium. Methods and Results:  Coupons of copper (C11000) and aluminium were inoculated with fungal isolates (Aspergillus spp., Fusarium spp., Penicillium chrysogenum and Candida albicans) for various time periods. Culture on potato dextrose agar and an in situ viability assay using the fluorochrome FUN‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 20 publications
4
55
0
1
Order By: Relevance
“…In contrast, growth of GPR was associated with the absence of chromium, nickel, and iron. Engineered materials may play a part, since it has been shown that some metals, such as zinc or copper, can modulate activity of bacteria and viruses (2) and of fungi (2,50). More generally, copper tends to be considered an alternative antimicrobial surface (17).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, growth of GPR was associated with the absence of chromium, nickel, and iron. Engineered materials may play a part, since it has been shown that some metals, such as zinc or copper, can modulate activity of bacteria and viruses (2) and of fungi (2,50). More generally, copper tends to be considered an alternative antimicrobial surface (17).…”
Section: Discussionmentioning
confidence: 99%
“…implants) susceptible to microbial contamination [710]. The anti-microbial properties of Cu are also used by mammalian host cells as defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore many microorganisms can exist in viable but non-culturable state that can proliferate under suitable conditions. They are not isolated and identified by traditional cultured based method [40][41][42]. Chi and Li [41] measured the total bioaerosol concentrations by the non culture-based methods were 100 to 1000 times higher than those by the culture-based method.…”
Section: Discussionmentioning
confidence: 99%